SECURITY AND PRIVACY IN THE CONTEXT OF THE INTERNET OF THINGS - Oliveira, Leandro; Rizo, André Castro (Revista Interface Tecnológica, 2022)
The Internet of Things (loT) is a tool that uses technology to connect electronic devices to the internet, and thus, enable the reach of various functionality in the most diverse sectors of industry, retail, agribusiness, etc. Among the main benefits of loT are the increase in efficiency and productivity, provided by the automation of operations and tasks. However, Internet of Things can still present some challenges, for example the security and privacy of data and other information that is generated way too much by loT devices. In this perspective, the objective of the work is to demonstrate through a bibliographic survey the importance and risks related to security and privacy in the loT. Some alternatives were presented, such as the encryption used by blockchains and some models of authentication and authorization of users or devices that connect to the internet. It is possible to conclude that even if there are data protection and security tools, studies on this topic must advance, given that new vulnerabilities can arise at any time.